Analisis Kemampuan Akumulasi Polyfosfat pada Tiap Fase Pertumbuhan Isolat Bakteri Toleran Uranium - Mutmainnah, Heni; Rijal, Muhammad (Biosel Biology Science and Education, 2020)
Polyphosphate is a straight chain biopolymer consisting of tens to hundreds of phosphate residues that are linked by high energy phosphoanhydride bonds, polyphosphate plays an important role in the bioremediation process of uranium waste, especially in the process of uranium metal precipitation in bacterial cells. Some bacteria are known to have the potential to interact with uranium through redox transformation and bioprecipitation by releasing inorganic phosphate to bind uranium in the environment. Inorganic phosphate results from degradation of polyphosphates that accumulate in cells. This study aims to determine the ability of uranium-tolerant bacteria to accumulate polyphosphates during their growth phase. Measurements were made in 5 growth phases, namely the lag phase, the logarithmic phase, the beginning of the stationary phase, the stationary phase, and the stationary end. Quantitative analysis of polyphosphate accumulations was carried out using the Olsen & Dean method. The test results are known that the uranium-tolerant bacterial isolat is able to accumulate the most optimal polyphosphate in the stationary phase, especially at the 48th hour and the lowest polyP accumulation is found in the initial stationary phase at the 24th hour.